CNS Involvement in AML Patient Treated with 5-Azacytidine. (14th August 2014) - Vasilatou, Diamantina; Papageorgiou, Sotirios; Bazani, Efthymia; Prasouli, Athina; Economopoulou, Christina; Roumpakis, Christoforos; Karakitsos, Petros; Dimitriadis, George; Pappa, Vasiliki
Abstract : Central nervous system (CNS) involvement in acute myeloid leukemia (AML) is a rare complication of the disease and is associated with poor prognosis. Sometimes the clinical presentation can be unspecific and the diagnosis can be very challenging. Here we report a case of CNS infiltration in a patient suffering from AML who presented with normal complete blood count and altered mental status.